Effect of seed washing either alone or in combination with garlic extract and Knowin 50WP on quality of jute seeds (Asian Journal of Medical and Biological Research, 2016)
Efficacy of seed washing, garlic extract, prewashed seeds treated with garlic extract, Knowin 50 WP (Carbendazim) and prewashed seeds treated with Knowin 50WP were evaluated on seed borne fungi of jute seeds. Nine seed borne fungi were detected on both deshi and tossa jute seed samples collected from sadar upazilla of Barisal district viz., Macrophomina phaseolina, Botryodiplodia theobromae, Fusarium spp, Colletotrichum corchori, Curvularia lunata, Aspergillus flavus, A. niger, Penicillium spp. and Alternaria spp.. Physical seed washing and garlic extract were found effective against seed borne diseases of jute which significantly decrease the association of seed borne fungi from jute seeds. Prewashed seeds treated with garlic extract showed highest germination and highest reduction of seed borne mycoflora from desi and tossa jute seeds. Knowin 50WP or prewashed seeds treated with Knowin 50WP were found effective to reduce seed borne fungi from jute seeds. Highest vigor index was obtained in jute seedlings raised from prewashed seeds treated with Garlic or Knowin 50WP. Thus, prewashed seeds treated with Garlic or Knowin 50WP resulting significant reduction of seed-borne fungal population and enhancing seeding vigor.Asian J. Med. Biol. Res. June 2016, 2(2): 318-323